Sequence Analysis of the K13-Propeller Gene in Artemisinin Challenging Plasmodium falciparum Isolates from Malaria Endemic Areas of Odisha, India: A Molecular Surveillance Study. (16th March 2020) - Rana, Ramakanta; Ranjit, Manoranjan; Bal, Madhusmita; Khuntia, Hemant Kumar; Pati, Sanghamitra; Krishna, Sri; Das, Aparup
Abstract : Estimation of the spread and advancement of Plasmodium falciparum artemisinin-resistant parasites can be done by probing polymorphisms in the kelch ( Pfk13 ) domain (a validated molecular marker). This study aimed to provide baseline information for future artemisinin surveillance by analyzing the k13 -propeller domain in P. falciparum field isolates collected from 24 study areas in 14 malaria hot spots of Odisha (previously Orissa) during July 2018-January 2019. A total of 178 P. falciparum mono infections were assessed. An 849-base pair fragment encoding the Pfk13 propeller was amplified by nested polymerase chain reaction and sequenced in both directions (PCR). After DNA alignment with the 3D7 reference sequence, all samples were found to be wild type. It can be anticipated that malaria public health is not under direct threat in Odisha relating to ART resistance.